Burden of breast cancer in Cali, Colombia: 1962-2012 - Luis Eduardo Bravo; Luz Stella García; Edwin Carrascal; Jaime Rubiano (Instituto Nacional de Salud Pública, 2014)
Objective. To describe the behavior of breast cancer (BC) during the 1962-2012 period from information provided by the Cali Cancer Registry and the Municipal Health Secretariat of Cali. Materials and methods. The incidence trend (1962-2007) and mortality trend (1984-2012) for breast cancer was studied and relative survival (RS)(1995-2004) was estimated. Age-standardized incidence and mortality rates to the world population (ASIR(w)/ASMR(w)) were expressed per 100 000 persons-year. Their temporal trend was examined with the annual percent of change (APC), and the Cox model was used to analyze the variables that influenced the survival of women with breast cancer. Results. The risk of breast cancer significantly increased in Cali through the 1962-2007 period, with an APC =1.7(95%CI:1.4-2.0). The ASIR(w) of BC increased from 27.1 in 1962 to 48.0 in 2007 and currently there are more than 500 cases reported annually. The mortality for BC has remained stable since 1984; in the 2009-2012 period, the ASMR(w) was 14.2. The 5-year RS was 69% (95%CI:66-71) from 2000-2004 and 62% (95%CI:59-65) from 1995-1999. The risk of death (HR) from BC was greater in persons from lower socioeconomic strata (SES) than from higher SES, HR=1.9(95%CI:1.3-2.9) and in those older than 70 years vs. menor que 50, HR=1.6(95%CI:1.1-2.2). Conclusion. Mortality remained stable while incidence increased and survival improved, which may be associated with better detection and advances in treatment.